PENGEMBANGAN CITRA DESTINASI WISATA MELALUI INOVASI DIGITAL MENUJU DESA WISATA BERKELANJUTAN - Dewi, Eka Grana Aristyana; Baskara, Ida Bagus Gede; Evayanti, Ni Luh Putu Nestri; Asih, Ni Kadek Rita Astri; Putra, I Komang Yoga Gangga; Kanoko, F. Maheswara Jevero; Putra, I Kadek Pande Dheva Brahmantya; Yoga, I Putu Agus Tirta; Kumaraarta, Kadek Rian; Givari, I Made Ardian; Yoga, I Gede Prana; Yasa, I Gusti Agung Made Suparta; Purnawan, Nathanael Putrapratama; Sutresna, I Made (ABDI KAMI: Jurnal Pengabdian Kepada Masyarakat, 2024)
The Student Organization Capacity Building Program (PPK Ormawa) was implemented in Jehem Village due to its significant potential for natural and cultural tourism, which remains relatively unknown to tourists due to limited promotion and digital information access. Although designated as a tourist village, the lack of technological infrastructure and information management poses a primary challenge in attracting visitors. Technological innovation was selected as a solution to enhance the village's image, as digital technology allows tourism information to be more widely accessible to potential visitors and facilitates more efficient management. This program combines observation and interview methods to identify the village's needs and potential, as well as technology diffusion and substitution methods in its activities. Community engagement involved creating a tourism website, conducting social media management training, and establishing a Tourism Awareness Group (Pokdarwis) responsible for managing tourism activities. Outcomes achieved include increased tourist visits and the enhancement of local human resource capacity in utilizing digital technology for tourism promotion. The sustainability of this program is expected to be achieved through ongoing management by Pokdarwis, along with the maintenance of the established digital facilities.